STRENGTH CONSIDERATION ON CAR BODY MODIFICATION FOR PANORAMIC TRAIN - Harnany, Dinny; Adista, Reyhan K. A.; Syaifudin, Achmad; Putra, Ary Bachtiar Krishna; Priyambodo, Singgih (Jurnal Rekayasa Mesin, 2024)
Modifying the car body structure from the existing train to another car body type requires an analysis of several factors. The strength of the design due to overload and the durability of the structures due to operational loads need to be re-evaluated. Furthermore, stiffness analysis also needs to determine the characteristics of the structure when it is not loaded. This study numerically analyzed the considerations in selecting the structural steel profile for modification of the existing car body into a panoramic type using the ANSYS Workbench R19. The underframe structure can still be used, and other structures are modified with the UNP profile. The side wall, and roof are changed in shape and size following the glass design of the panoramic train. The solid 3D model is rebuilt into a surface model to simplify the analysis. Static structural analysis is used to clarify the strength of the design under overload, a combination of static and transient structural analysis is applied to calculate the operating life, and modal analysis is chosen to figure out the stiffness. The simulation results showed that the modified design had met the needs and requirements based on the PM 175 standard of 2015 by the Indonesian Ministry of Transportation and the international standard EN-12663.